Zircon luminescence dating revisited - Schmidt, Christoph; Halter, Théo; Hanson, Paul R.; Ulianov, Alexey; Putlitz, Benita; King, Georgina E.; Kreutzer, Sebastian (Geochronology, 2024)
Luminescence dating plays a pivotal role in Quaternary science, yet ongoing methodological challenges persist in refining the temporal range, accuracy, and precision of luminescence methods. Our contribution revisits zircons as potential alternative dosimeters to quartz, feldspar, or calcite for routine dating applications. The essential advantage of zircons over other minerals is the time-invariant and high internal dose rate due to high radionuclide contents, dominating over the external contribution, which is more challenging to assess. Reported drawbacks are low zircon abundance, laborious sample preparation, signal instabilities, unknown optical signal resetting rates, and low signal intensities. Our present study uses modern luminescence detection equipment and analytical methods to investigate mineral separation, mineral characteristics, bleachability, signal spectra and intensities, and the potential to auto-regenerate signals. We present results for two zircon samples that are different in provenance, trace element composition, and luminescence characteristics, each of them containing a couple of hundred grains. Optically stimulated luminescence (OSL) signal resetting rates of zircon in response to simulated sunlight exposure are orders of magnitudes faster than for feldspar and slightly slower than for quartz. The recorded thermoluminescence (TL) spectra confirm previously published results with luminescence emissions in the UV/violet and red wavelength range, supplemented by narrowband emissions associated with rare earth element (REE) dopants. Storage experiments of single zircon grains for auto-regenerated measurements over 1.5 years yielded very low OSL signals. At the same time, after only 3 weeks, we measured acceptable TL signal intensities at the cost of lower bleaching rates. To date, the auto-regeneration approach seems to be a promising and accurate approach to dating zircon light exposure events, especially when combining the natural OSL with auto-regenerated TL. However, further studies are required to optimise signal intensities and establish zircons as viable targets for routine dating applications.